Opportunities and Challenges of Small Molecule Induced Targeted Protein Degradation - He, Ming; Lv, Wenxing; Rao, Yu (Frontiers in Cell and Developmental Biology, 2021)
PROTAC represents a new type of small molecule induced protein degradation technology that has emerged in recent years. PROTAC uses bifunctional small molecules to induce ubiquitination of target proteins and utilizes intracellular proteasomes for chemical knockdown. It complements the gene editing and RNA interference for protein knockdown. Compared with small molecule inhibitors, PROTAC has shown great advantages in overcoming tumor resistance, affecting the non-enzymatic function of target proteins, degrading undruggable targets, and providing new rapid and reversible chemical knockout tools. At the same time, its challenges and problems also need to be resolved as a fast-developing newchemical biology technology.